2005
DOI: 10.1021/bi047886u
|View full text |Cite
|
Sign up to set email alerts
|

Active-Site Specificity of Digestive Aspartic Peptidases from the Four Species of Plasmodium that Infect Humans Using Chromogenic Combinatorial Peptide Libraries

Abstract: Two targeted chromogenic octapeptide combinatorial libraries, comprised of 38 pools each containing 361 different peptides, were used to analyze the enzyme/substrate interactions of five plasmepsins. The first library (P1 library) was based on a good synthetic aspartic peptidase substrate [Westling, J., Cipullo, P., Hung, S. H., Saft, H., Dame, J. B., and Dunn, B. M. (1999) Protein Sci. 8, 2001-2009 Scarborough, P. E., and Dunn, B. M. (1994) Protein Eng. 7, 495-502] and had the sequence Lys-Pro-(Xaa)-Glu-P1*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 43 publications
(83 reference statements)
4
52
0
Order By: Relevance
“…For the other malarial enzymes, the K i values for the F2A mutant were no more than 3-fold higher or lower than wild-type. Current structural and substrate studies are consistent with the results of the F2A mutant (35). The structure of the uncomplexed PfPM2 revealed that the active site of PfPM2 is larger than commonly assumed based on structures of the enzyme in complex with inhibitors (36).…”
Section: N-terminal Mutationssupporting
confidence: 76%
“…For the other malarial enzymes, the K i values for the F2A mutant were no more than 3-fold higher or lower than wild-type. Current structural and substrate studies are consistent with the results of the F2A mutant (35). The structure of the uncomplexed PfPM2 revealed that the active site of PfPM2 is larger than commonly assumed based on structures of the enzyme in complex with inhibitors (36).…”
Section: N-terminal Mutationssupporting
confidence: 76%
“…The peptide specificity assay was described in more detail elsewhere (18). Briefly, an aliquot of each pool of the P1 and P1Ј libraries giving a total peptide concentration of ϳ100 M was used in a spectrophotometric assay.…”
Section: Methodsmentioning
confidence: 99%
“…Like these HIV-1 aspartyl protease inhibitors, most Plm I and II inhibitors mimic the tetrahedral intermediate formed during the aspartyl protease catalysis. There are several transition state analogue cores used for the design of Plm inhibitors [35,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], but the most important include the statine core [54,56,57,64], the reversed-statine core [53,54], or a hydroxyethylamine motif (Fig. 4) [56,61,62].…”
Section: Aspartyl Proteases (Plasmepsins)mentioning
confidence: 99%
“…(4). Transition-state mimicking groups in peptidomimetic plasmepsin inhibitors: reduced amine [52,59], statine [54,56,57,64], hydroxypropylamine [51], reversed-statine [53,54], dihydroxyethylene (C-and N-duplicated) [35,55,63], norstatine [58,60,65], and hydroxyethylamine [56,61,62].…”
Section: Aspartyl Proteases (Plasmepsins)mentioning
confidence: 99%